Work life balance and pro environmenal behavior on sustainability - Nurhasanah, Nurhasanah; Tiyasiningsih, Ezky (Journal of Economics and Business Letters, 2024)
This study investigates the impact of work-life balance (WLB) and pro-environmental behavior (PEB) on sustainability outcomes in Indonesia's manufacturing sector. As sustainability becomes increasingly important within industrial settings, understanding the role of human-centric factors like WLB and PEB can offer unique insights into achieving sustainable practices. Data were collected from 278 employees across the top four manufacturing companies in Indonesia. Using Structural Equation Modeling (SEM) via LISREL, the study demonstrates that both WLB and PEB significantly contribute to perceived sustainability outcomes. The results indicate that employees who experience a healthy work-life balance are more likely to engage in behaviors that support environmental initiatives, ultimately enhancing organizational sustainability. These findings suggest that promoting a supportive work environment and encouraging eco-friendly behaviors can facilitate sustainable business practices. The study’s implications highlight the importance of integrating employee well-being into sustainability strategies within manufacturing industries, providing actionable recommendations for managers and policymakers aiming to foster sustainable development.